Equisingularidade de curvas planas irredutíveis sobre corpos de característica arbitrária - Orlando Catarino da Silva (2009)
Two irreducible algebroid plane curves are equisingular if and only if they have the same semigroup values. In this work we study equisingularity of irreducible algebroid plane curves on fields with arbitrary characteristic. We present methods to obtain the semigroup associated to a irreducible plane curves are equisingular if and only if they have the same multiplicity sequence in its canonical resolution